(untitled) (Al-Mansour Journal, 2022)
Price support policy considered as one of the most important manner in which government intervention application in most developed and under developed countries. A hope was given from this policy to improve and increase agricultural production and provide food for major population with fixed price levels which enable consumer with low income to pay for his commodities, and to participate in providing capital accumulation, which is very important in developing process .the question here is if this price policy achieved its goals or not?